Oral sinensetin, but not nobiletin alone, prevents MK801‐induced impairment of memory formation in mice, like nobiletin‐rich chinpi, a kampo medicine. Issue 2 (15th July 2017) - Sun, Wen; Kawahata, Ichiro; Xu, Huinan; Yoshida, Masaaki; Ando, Hidehiro; Yokosuka, Akihito; Mimaki, Yoshihiro; Yamakuni, Tohru
ABSTRACT: Aim: Our pilot clinical study suggested that nobiletin‐rich Citrus reticulata peel, also known as nchinpi, has the potential to be beneficial as a kampo medicine for Alzheimer's disease. The nchinpi extract has a high content of polymethoxyflavones, including nobiletin and sinensetin. Our previous pharmacological study using cultured hippocampal neurons showed that the nchinpi extract more potently facilitated cAMP‐response element (CRE)‐mediated transcription associated with long‐term memory formation than did nobiletin alone, via a mechanism in which nobiletin and four other polymethoxyflavones, one being sinensetin, a potently CRE‐mediated transcription‐facilitating substance, cooperated. It remained unclear, however, whether nchinpi could be more effective in vivo in preventing memory deficits than could nobiletin alone. Here, we compared the impacts of the respective samples on N ‐methyl‐D‐aspartate receptor antagonism‐induced learning and memory disability. Methods: The nchinpi extract or nobiletin was orally given to mice for 7 consecutive days to examine their respective impacts on this impairment on contextual fear conditioning test. In a separate analysis, sinensetin's impact was evaluated. Results: Nchinpi extract at a dose corresponding to that of 25 mg/kg/day nobiletin prevented impaired memory formation, whereas nobiletin failed to exhibit such beneficial effects even when given at 50 mg/kg/day. Oral sinensetin prevented memory deficits at 25 mg/kg/day, unlike nobiletin. Conclusion: Nchinpi acting in a multicomponent drug‐like fashion in vitro has an obvious advantage over nobiletin alone in the ability to prevent memory dysfunction in animals as well and, hence, might be beneficial in patients with dementia.